Pioneer Rocketry - 2016 WSGC Collegiate Rocket Competition - Guither, Adrian (Proceedings of the Wisconsin Space Conference, 2017)
The objective of the 2016 Wisconsin Space Grant Consortium Collegiate Rocket Launch Competition was to design and build a â€œtrue scale modelâ€ of any real world rocket or missile. We selected to bring a scale model of the Orbital ATK Pegasus XL to this year's competition. We had three flights during the competition, all of which were successful, and close to our expected values. This, as well as our documentation, earned us first place in this year's competition. The following report details the design and construction of Pioneer Rocketryâ€™s 2016 competition rocket, along with information regarding Pioneer Rocketryâ€™s growth as both an educational and professional organization.